2005
DOI: 10.1148/radiol.2352031718
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis: Assessment of Bowel Viability with Color Doppler US

Abstract: Color Doppler US is more accurate than abdominal radiography in depicting bowel necrosis in NEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
217
2
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(239 citation statements)
references
References 19 publications
5
217
2
15
Order By: Relevance
“…It results showed a higher sensitivity and specificity of color Doppler ultrasound, suggesting that this study is part of the initial assessment of any neonate with clinical features sugges- tive of necrotizing enterocolitis. It was found that the absence of flow in the intestinal wall, suggesting ischemia, and increased vascularization of the same, indicating an inflammatory process incipient, are aspects that facilitate the clinical management early [24].…”
Section: Gray Scale and Color Doppler Ultrasoundmentioning
confidence: 99%
“…It results showed a higher sensitivity and specificity of color Doppler ultrasound, suggesting that this study is part of the initial assessment of any neonate with clinical features sugges- tive of necrotizing enterocolitis. It was found that the absence of flow in the intestinal wall, suggesting ischemia, and increased vascularization of the same, indicating an inflammatory process incipient, are aspects that facilitate the clinical management early [24].…”
Section: Gray Scale and Color Doppler Ultrasoundmentioning
confidence: 99%
“…Color Doppler U/S may be useful in determining bowel viability, which can be characterized by bowel wall thickness and perfusion. 13,14 Determining the viability by differentiating ischemic from necrotic bowel is not possible using the current radiographic method. Color Doppler detection of absent blood flow showed 100% sensitivity, which is far greater than that of radiographic detection of peritoneal free air (40%) as a positive sign for severe NEC with necrotic bowel (P ¼ 0.3).…”
Section: Ultrasonographymentioning
confidence: 99%
“…Color Doppler detection of absent blood flow showed 100% sensitivity, which is far greater than that of radiographic detection of peritoneal free air (40%) as a positive sign for severe NEC with necrotic bowel (P ¼ 0.3). 14 In NEC, inflammation causes initial hyperemia in the bowel wall, which is followed by ischemia and bowel wall thinning. This progression of NEC, which was confirmed by color Doppler U/S evidence, 13 is illustrated in Figure 3.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Bowel ultrasonography provides an opportunity for the evaluation of bowel dynamics as well as free intra-abdominal fluid. Many studies have emphasized the higher diagnostic accuracy of gray-scale and Doppler ultrasonography over plain abdominal radiography for the detection of some bowel wall changes, especially those in bowel wall thickness, echogenicity, and perfusion, as well as portal venous gas and focal or free intra-abdominal fluid [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%